Optical properties and sugar content determination of commercial carbonated drinks using surface plasmon resonance - Wan Yusoff, Wan Yusmawati; Chuah, H. P.; Mat Yunus, Wan Mahmood (Science Publications, 2007)
In this study, an optical sensor based on Kretschmann SPR technique was used to detect the sugar content in commercial carbonated drinks. Three samples of carbonated drinks labeled as "Coke", "100 Plus" and "F&N Orange" have been chosen for angle scan SPR measurements. All the measurements were carried out at room temperature using He-Ne laser beam (632.8nm, 5mW) as a light source. The commercially available carbonated samples were diluted by adding distilled water to produce solutions with different sugar content. The results show that the shift of resonance angle (δ;θSPP) increases linearly with the sugar content in which the detection limit and sensor sensitivity could be quantified. Therefore, this technique could be used as optical sensor for detecting sugar content in carbonated soft drinks.